2003
DOI: 10.1165/rcmb.2002-0153oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Impairs Antibacterial Function of Macrophages Through Effects on Actin

Abstract: Oxidative stress may impair alveolar macrophage function in patients with inflammatory lung diseases or those exposed to high concentrations of oxygen. We investigated putative mechanisms of injury to macrophages by oxidative stress, using RAW 264.7 cells exposed to 95% oxygen for 48 h. Hyperoxia-exposed macrophages were less able to phagocytose and kill Klebsiella pneumoniae than normoxic controls, despite increased production of nitric oxide, a free radical important in pathogen killing. Exposure of macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 54 publications
11
75
0
Order By: Relevance
“…They concluded that oxidative stress impairs macrophage antibacterial function through effects on actin. [24]. Although the methods used in the present study did not permit us to examine bacterial killing, we have previously demonstrated that hyperoxia impairs bacterial killing in human monocytes [31].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…They concluded that oxidative stress impairs macrophage antibacterial function through effects on actin. [24]. Although the methods used in the present study did not permit us to examine bacterial killing, we have previously demonstrated that hyperoxia impairs bacterial killing in human monocytes [31].…”
Section: Discussionmentioning
confidence: 81%
“…ROS can cause oxidation and inactivation of a variety of macromolecules in the lung including proteins, lipids and DNA [19][20]. Several studies of cells in culture have shown that cells are injured by the detrimental effects of hyperoxia [21][22][23][24][25][26]. In addition, animal models and human trials have demonstrated that exposure to prolonged hyperoxia is associated with the development of acute lung injury and the progression to chronic lung disease [1].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already demonstrated oxidation of the cytoskeletal protein actin in different models [36,37]. The complex modifications induced by ROS on muscle actin are characterised by severe disruption of the actin filaments, hampering their interaction with the myosin protein [38], thus suggesting that oxidation of contractile actin may contribute to muscle dysfunction in these models [36,38].…”
Section: Diaphragm Carbonylated Proteinsmentioning
confidence: 99%
“…These results indicate that moderate concentrations of H 2 O 2 can restore normal formation of filopodia and lamellipodia in hyperoxic macrophages. Studies from our and other laboratories have shown that actin oxidation plays a critical role in the compromised macrophage phagocytosis under hyperoxic conditions (O'Reilly et al, 2003;Morrow et al, 2007). To address whether H 2 O 2 affects macrophage function via altering actin oxidation, the extent of carbonyl formation was assessed in immunoprecipitated total actin protein isolated from RAW cells as described previously by Morrow et al (2007).…”
Section: H 2 O 2 Reduces Hyperoxia-induced Actin Oxidationmentioning
confidence: 99%
“…Excessive amounts of reactive oxygen species (ROS) have been shown to mediate pathogenesis of various pulmonary diseases and tissue injury (Ciencewicki et al, 2008). Toxic levels of ROS generated under hyperoxic conditions can compromise phagocytic function of AMs (O'Reilly et al, 2003;Morrow et al, 2007). Besides superoxide, hydrogen peroxide (H 2 O 2 ) is another form of ROS that is generated under hyperoxic conditions (Turrens et al, 1982).…”
Section: Introductionmentioning
confidence: 99%